FOOD GUIDELINES FOR HIGH SCHOOL VOLLEYBALL PLAYERS IN THE DEMONSTRATION SCHOOL UNDER THE MINISTRY OF HIGHER EDUCATION, SCIENCE, RESEARCH AND INNOVATION - Meesanga, Sirachach; Peeraphatchara , Chutamas; Thongkham, Chukkrit (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
Adequate and nutritionally appropriate dietary intake plays a pivotal role in maintaining optimal physiological readiness in athletes, which is essential for sustaining the intensity of training and competitive performance. This study employed a mixed-methods research design, integrating both quantitative and qualitative approaches. The quantitative component involved a structured questionnaire, while the qualitative dimension encompassed in-depth interviews and focus group discussions. The objectives of this study were: (1) to investigate the dietary behaviors of high school volleyball athletes, and (2) to develop and propose evidence-based dietary guidelines tailored to the specific needs of this athletic population. The study population comprised 250 high school volleyball athletes enrolled in demonstration schools under the jurisdiction of the Office of the Permanent Secretary, Ministry of Higher Education, Science, Research, and Innovation. Purposive sampling was used to select 14 student-athletes and 9 subject-matter experts who participated in qualitative data collection. Research instruments included a validated dietary behavior questionnaire, a 24-hour dietary recall form, and an evaluative tool assessing the relevance and feasibility of the proposed dietary guidelines. Data were analyzed using descriptive statistics, including means and standard deviations, as well as thematic content analysis for qualitative data. Findings indicated that: (1) athletes’ overall dietary behavior was at a moderate level; (2) the average daily caloric intake based on the 24-hour recall was 1,461 kilocalories, substantially lower than the recommended daily intake of 2,400 kilocalories; and (3) the proposed dietary guidelines consisted of three strategic components: nutrition education recommendations, a structured dietary guideline manual, and engagement in supportive nutritional promotion activities. The proposed framework was assessed to be highly appropriate and feasible. The study recommends the implementation of targeted nutritional education interventions and the integration of student satisfaction assessments to inform the ongoing development of school-based meal programs for student-athletes.